Analysis of Google Translate Results in the Lyrics of "Rewrite the Stars" by Anne-Marie and James Arthur - Mutiara Komalasari (English Language and Education Spectrum, 2024)
There are numerous language varieties in the world, necessitating translation for comprehension. Google Translate serves as a free online translation tool available in various languages. It can be utilized for translating text, documents, websites, including song lyrics, with extensive coverage and unlimited access. However, Google Translate often produces inaccurate meanings. This research aims to identify errors generated by Google Translate in translating the lyrics of "Rewrite the Stars" by Anne-Marie and James Arthur. The researcher employs a qualitative descriptive research method, using the lyrics obtained from Google and translated into Indonesian using Google Translate. The analysis of Google Translate errors in the lyrics is based on Tono et al.'s (2014) theory. The study reveals a total of 15 translation errors in the lyrics, classified into four categories: three omissions, four additions, six selection errors, and two arrangement errors. The majority of translation errors result from meaning discrepancies. Therefore, it is crucial to verify Google Translate results before using them.